2021
DOI: 10.21272/bel.5(1).6-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Educational Leadership and the Innovative Strategies Engaging Online Faculty for the Excellent Teaching Performance in the United States

Abstract: This research paper summarizes the arguments and counterarguments within the scientific discussion on the transformational educational leadership and the innovative strategies engaging online faculty for the excellent teaching performance in the United States. There are various leadership traits of academic leadership to assess engagement amongst online adjunct faculty in the online platform of higher education. This research study focuses on the lived experiences of academic leaders to aid online adjunct facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…An essential stage in the formation of a quality education system is to ensure the relationship between SDG 4 "Quality education" and other goals of sustainable development [4,8,9,18,24,34,36,37], especially with SDG 8 "Decent work and economic growth". Such an integrated approach made it possible to see the prospects for the development of both the quality assurance system as a whole (using the examples of universities) and individual educational programs [5,10,11,16,21,28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…An essential stage in the formation of a quality education system is to ensure the relationship between SDG 4 "Quality education" and other goals of sustainable development [4,8,9,18,24,34,36,37], especially with SDG 8 "Decent work and economic growth". Such an integrated approach made it possible to see the prospects for the development of both the quality assurance system as a whole (using the examples of universities) and individual educational programs [5,10,11,16,21,28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, it opens up prospects for redistribution of market positions and change of business leaders (Parviainen et al, 2017). The significant impact of digitalization is reflected in the transformation of methods and tools used in education (Lopez et al, 2020;Ugur, 2020;Matos & Kasztelnik, 2021;Pettersson, 2021). Much attention is also paid to the study of information technology in public life and the social effect they cause (Bardy & Rubens, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same context, Grunefeld (2020) indicated that educational leadership includes communication skills, decision-making, inspiration, time management, self-management, and commitment. Thus, universities need to be led rationally and effectively by practicing transformational leadership behaviors that enhance communication and interaction processes, as well as planning and participation in decision-making (Matos & Kasztelnik, 2021). Nicdao (2019) indicated that one of the leadership styles produced by scientific progress and technical development is the transformational leadership style, which is distinguished by its high ability to lead universities in the face of modern challenges and developments by influencing the development of their system and increasing the organizational creativity of transformational leaders.…”
Section: Introductionmentioning
confidence: 99%